Pemetaan Sentra Produksi Telur Asin Kabupaten Brebes berbasis Sistem Informasi Geografis - Humam, Mohammad; Nishom, M; Sasmito, Ginanjar Wiro (Sinkron : jurnal dan penelitian teknik informatika, 2018)
Brebes is one of the districts in Central Java Province which is famous for its salted egg production. However, the Brebes Regency government does not have data on salted egg production centers that are publicly published and integrated with each other, either in the form of profile data, geographic map data, route data, production data, production reports, and other supporting data, such as data on salted egg producers, income produced, and the amount of production produced every month. Lack of information on salted egg production centers delivered to the general public, causing several centers of salted egg production in Brebes Regency to be less well known by the wider community. For this reason, a system that can publish the production center is a solution to the existing problems. System development method in this study uses the concept of System Development Life Cycle (SDLC), and for the software development process Rapid Application Development (RAD) is based on codeigniter framework as a development tool. The results of this study are Geographic Information Systems (GIS) which can provide information on salted egg production centers in Brebes regency with attractive visualization so that it can be used as a medium to display data on salty egg production centers dynamically as well as promotional media, so that they can expand their share. market, this is because the system built can display profile data, geographic map data, route data and production data that are integrated with the Brebes Regency government website.